Genome-wide identification, molecular evolution, and expression analysis of auxin response factor (ARF) gene family in Brachypodium distachyon L - Liu, Nannan (BMC Plant Biol, 2018)
BACKGROUND: The auxin response factor (ARF) gene family is involved in plant development and hormone regulation. Although the ARF gene family has been studied in some plant species, its structural features, molecular evolution, and expression profiling in Brachypodium distachyon L. are still not clear. RESULTS: Genome-wide analysis identified 19 ARF genes in B. distachyon. A phylogenetic tree constructed with 182 ARF genes from seven plant species revealed three different clades, and the ARF genes from within a clade exhibited structural conservation, although certain divergences occurred in different clades. The branch-site model identified some sites where positive selection may have occurred, and functional divergence analysis found more Type II divergence sites than Type I. In particular, both positive selection and functional divergence may have occurred in 241H, 243G, 244 L, 310 T, 340G and 355 T. Subcellular localization prediction and experimental verification indicated that BdARF proteins were present in the nucleus. Transcript expression analysis revealed that BdARFs were mainly expressed in the leaf and root tips, stems, and developing seeds. Some BdARF genes exhibited significantly upregulated expression under various abiotic stressors. Particularly, BdARF4 and BdARF8 were significantly upregulated in response to abiotic stress factors such as salicylic acid and heavy metals. CONCLUSION: The ARF gene family in B. distachyon was highly conserved. Several important amino acid sites were identified where positive selection and functional divergence occurred, and they may play important roles in functional differentiation. BdARF genes had clear tissue and organ expression preference and were involved in abiotic stress response, suggesting their roles in plant growth and stress resistance. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (10.1186/s12870-018-1559-z) contains supplementary material, which is available to authorized users.